Valoración agronómica de diez accesiones de trigo (Triticum sp.) harinero y duro, para el proyecto UEB-FIASA, Laguacoto III, provincia Bolívar, segunda campaña de siembra - Azogue Martínez, Darwin Alejandro (2025)
Wheat is one of the most relevant crops worldwide. However, in Bolívar Province, wheat productivity faces significant challenges due to phytosanitary issues, particularly affecting small and medium-scale producers. In this context, the present research aimed to evaluate agronomic and sanitary traits of hard and soft wheat accessions to identify those best adapted and most productive under the agroecological conditions of Laguacoto III. The objectives of this study were: i) Characterize the agronomic components of the hard and soft wheat accessions; ii) Determine the severity of diseases affecting the evaluated accessions; iii) Assess the adaptation of the wheat accessions based on their yield. The treatments consisted of ten accessions (five hard wheat and five soft wheat), analyzed using a randomized complete block design (RCBD) with three replicates. Analyses included analysis of variance, Tukey's test at 5%, and correlation analysis. The variables evaluated included: percentage of emergence (PE), plant height (AP), severity of foliar spots (SMF), severity of Fusarium (SF), days to heading (DE), number of grains per spike (NGE), hectoliter weight (PH), thousand-grain weight (PMG), and yield (RT), among others. The results showed that the hard wheat accessions A-03 and A-01 presented lower severity of foliar spots (61.48% and 63.15%, respectively), while among soft wheat, H-04-UEB stood out for its greater height (111.3 cm) and adaptive potential. Additionally, significant differences in total yield (RT) were identified among the hard wheat treatments, highlighting the impact of management and local conditions. In conclusion, the hard wheat accessions A-03 and A-01, and the soft wheat accession H-04-UEB, are promising for use in breeding programs due to their favorable agronomic and sanitary performance under the study conditions. These results provide a solid foundation for future research and management strategies in wheat production in Bolívar Province.